Targeting S. aureus Extracellular Vesicles: A New Putative Strategy to Counteract Their Pathogenic Potential - Giulio Petronio Petronio; Maria Di Naro; Noemi Venditti; Antonio Guarnieri; Marco Alfio Cutuli; Irene Magnifico; Alessandro Medoro; Emanuele Foderà; Daniela Passarella; Daria Nicolosi; Roberto Di Marco (MDPI AG, 2024)
Long-term inflammatory skin disease atopic dermatitis is characterized by dry skin, itching, and eczematous lesions. During inflammation skin barrier protein impairment promotes S. aureus colonisation in the inflamed skin, worsening AD patient's clinical condition. Proteomic analysis revealed the presence of several immune evasion proteins and virulence factors in S. aureus extracellular vesicles (EVs), suggesting a possible role for these proteins in the pathophysiology of atopic dermatitis. The objective of this study is to assess the efficacy of a wall fragment obtained from a patented strain of C. acnes DSM28251 (c40) and its combination with a mucopolysaccharide carrier (HAc40) in counteract the pathogenic potential of EVs produced by S. aureus ATCC 14458. Results obtained from in vitro studies on HaCaT keratinocyte cells showed that HAc40 and c40 treatment significantly altered the size and pathogenicity of S. aureus EVs. Specifically, EVs grew larger, potentially reducing their ability to interact with the target cells and decreasing cytotoxicity. Additionally, the overexpression of the tight junctions mRNA zona occludens 1 (ZO1) and claudin 1 (CLDN1) following EVs exposure was decreased by HAc40 and c40 treatment, indicating a protective effect on the epidermal barrier's function. These findings demonstrate how Hac40 and c40 may mitigate the harmful effects of S. aureus EVs. Further investigation is needed to elucidate the exact mechanisms underlying this interaction and explore the potential clinical utility of c40 and its mucopolysaccharide carrier conjugate HAc40 in managing atopic dermatitis.